Comparative Confocal and Histopathological Study of Corneal Changes in Multiple Myeloma. Issue 1 (January 2017) - Micali, Antonio; Roszkowska, Anna M.; Postorino, Elisa I.; Rania, Laura; Aragona, Emanuela; Wylegala, Edward; Nowinska, Anna; Ieni, Antonio; Calimeri, Sebastiano; Pisani, Antonina; Aragona, Pasquale; Puzzolo, Domenico
Abstract : Purpose: Corneal opacities rarely occur in multiple myeloma (MM). Our study correlates the findings of in vivo confocal microscopy (IVCM), a useful diagnostic tool, with histopathological features of corneal opacities appearing in a patient with MM. Methods: Case report. Results: A 53-year-old man developed corneal opacities in both eyes, more pronounced in the left eye. After IVCM examination, he underwent penetrating keratoplasty in the left eye, and the button was processed for light and electron microscopy and immunohistochemistry. The diagnosis of MM was made, as confirmed by the elevation of IgGk light chains. IVCM demonstrated hyperreflective areas at the epithelial level, hyperreflective keratocytes of dendritic and lamellar morphology in whole stroma, and hyperreflective endothelial cells. Histopathological examination disclosed many vacuoles in the epithelial cell cytoplasm and a homogenous granular material in the Bowman layer. In stroma, keratocytes of different shape and size, with vesicles laden with an abnormal material, were evident. In Descemet membrane, the posterior nonbanded zone had a honeycomb appearance because of the presence of many roundish spaces among wide-spaced collagen fibers. Endothelial cells demonstrated vesicles filled with a material of uneven electron density. Immunohistochemical analysis showed strong positivity for IgGk light chains in keratocytes and among stromal lamellae. Conclusions: This is the first study describing a correspondence between IVCM features and histopathological alterations observed in corneal opacities in MM. The results of this study improve the current understanding of the pictures obtained by IVCM studies.